HYDRODYNAMIC ANALYSIS OF BIONIC CHIMERICAL WING PLANFORMS INSPIRED BY MANTA RAY EIDONOMY - Arash Taheri (Indonesian Journal of Engineering and Science (IJES), 2021)
In this paper, inspired by the external morphology of a manta ray (Mobula alfredi), four chimerical wing planforms are designed to assess its gliding performance. The planforms possess an arbitrary combination of extra hydrodynamic features like tubercles at the leading edge (L.E.) and trailing edge (T.E.) inspired by humpback whale's flippers and flukes, respectively, as longitudinal ridges inspired by whale shark's economy. In addition, another planform is designed to investigate the possible effects of manta ray's injuries (geometric deficiency) generated by predator's attacks or boat strikes on its locomotion (gliding) performance. In this regard, turbulent flow physics involved in the problem is numerically simulated at different angles of attack (AoA). High Reynolds number, 106, corresponding to the swimming of a  juvenile manta ray at an average speed equals one m/s. The results show that the manta ray-inspired planform with L.E. undulations exhibits a superior performance at high AoAs than its other counterpart variants. In addition, the results demonstrate that injuries on the manta ray's body can noticeably modify hydrodynamics and, as a result corresponding hydrodynamical forces and moments acting on the swimming animal in the gliding phase.